1985
DOI: 10.1128/jvi.53.3.786-792.1985
|View full text |Cite
|
Sign up to set email alerts
|

In vitro phenotypic markers of a poliovirus recombinant constructed from infectious cDNA clones of the neurovirulent Mahoney strain and the attenuated Sabin 1 strain

Abstract: Infectious cDNA corresponding to the entire genome of the attenuated Sabin strain of type 1 poliovirus has been inserted into EcoRI site of bacterial plasmid pBR325. Two consecutive PstI fragments (nucleotide positions 1814 to 3421) of the infectious cDNA of the Sabin 1 strain were replaced by the corresponding DNA fragments prepared from an infectious DNA clone of the genome of the virulent Mahoney strain of poliovirus type 1. The exchanged segment encodes capsid protein VP1 and part of capsid protein VP3, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 29 publications
(25 reference statements)
4
47
0
Order By: Relevance
“…The reason for the ts phenotype of the RIPO constructs described here, however, remains to be elucidated. As expected, the PVS(RIPO) ts phenotype is associated with mutations in two PV1(S) components as the capsid and 3D pol RNA polymerase are known to be determinants of this genetic trait [Kohara et al, 1985;Paul et al, 2000]. The very pronounced ts phenotype of the RIPO constructs in cells of neuronal origin co-varies with the remarkable attenuation phenotype of these constructs in CD155 tg mice, which leads us to speculate that ts of viral replication contributes to attenuation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The reason for the ts phenotype of the RIPO constructs described here, however, remains to be elucidated. As expected, the PVS(RIPO) ts phenotype is associated with mutations in two PV1(S) components as the capsid and 3D pol RNA polymerase are known to be determinants of this genetic trait [Kohara et al, 1985;Paul et al, 2000]. The very pronounced ts phenotype of the RIPO constructs in cells of neuronal origin co-varies with the remarkable attenuation phenotype of these constructs in CD155 tg mice, which leads us to speculate that ts of viral replication contributes to attenuation.…”
Section: Discussionsupporting
confidence: 58%
“…Attenuation of the Sabin vaccine strain PV1(S) is prominently associated with a ts phenotype [Lwoff, 1959;Kohara et al, 1985]. In search of hitherto unknown attenuation markers of the chimeric RIPO polioviruses, we determined the growth phenotypes of PV1(RIPO), PV1(RIPOS), and PVS(RIPO) and compared them with wt PV1(M).…”
Section: Growth Phenotypes Of Pv/hrv2 Ires Chimera In Tissue Culture mentioning
confidence: 99%
“…Temperature sensitivity is a hallmark of many successful liveattenuated vaccines and was historically a criterion to confirm attenuation of Sabin OPV vaccine stocks prior to release by manufacturers 40 . The temperature-sensitivity growth profile of nOPV2-CD mirrored that of Sabin OPV2 in Vero cells, with replicative fitness declining as temperature was increased from 33°C to 38.5°C ( Fig.…”
Section: Codon-deoptimized Nopv2 Exhibits Reduced Replicative Fitnessmentioning
confidence: 99%
“…To identify the genome regions that influence the neurovirulence or attenuation phenotype of poliovirus type 1, a number of recombinant viruses were constructed in vitro between the Mahoney and the Sabin 1 strains by using infectious cDNA clones of the two strains (11,13,25). Monkey neurovirulence tests on these recombinant viruses (13,25) revealed that the genome region of nucleotide positions 1 to 1,122, including mainly the 5' noncoding redion, harbors a relatively strong determinant(s) influencing the neurovirulence or attenuation phenotype, and that determinants weakly influencing the phenotye were spread over several areas of the entire viral genome including most of the viral capsid precursor protein region.…”
Section: The Attenuationmentioning
confidence: 99%
“…Monkey neurovirulence tests on these recombinant viruses (13,25) revealed that the genome region of nucleotide positions 1 to 1,122, including mainly the 5' noncoding redion, harbors a relatively strong determinant(s) influencing the neurovirulence or attenuation phenotype, and that determinants weakly influencing the phenotye were spread over several areas of the entire viral genome including most of the viral capsid precursor protein region. These results led to speculations that the rate of viral multiplication in the central nervous system might be one of the important factors determining the neurovirulence phenotype, and that virion surface characteristics such as antigenicity and immunogenicity have a little correlation with neurovirulence (11,22,25).…”
Section: The Attenuationmentioning
confidence: 99%